Plasma Epstein–Barr Viral Deoxyribonucleic Acid Predicts Worse Outcomes in Pediatric Nonmetastatic Nasopharyngeal Carcinoma Patients: An Observational Study of 89 Cases in an Endemic Area. Issue 50 (December 2015) - Shen, Ting; Tang, Lin-Quan; Gu, Wei-Guang; Luo, Dong-Hua; Chen, Qiu-Yan; Li, Pei-Jing; Mai, Dong-Mei; Mai, Hai-Qiang; Mo, Hao-Yuan
Abstract : Abstract: To evaluate the clinical significance of pretreatment levels of plasma Epstein–Barr virus DNA (pEBV DNA) on prognoses in pediatric nasopharyngeal carcinoma (NPC) patients. Eighty-nine patients aged 21 years old or younger with nonmetastatic NPC were evaluated to determine the effect of pEBV DNA levels on progression-free survival (PFS), distant metastasis-free survival (DMFS), and overall survival (OS). Survival probabilities in patient groups that were segregated by clinical stage or pEBV DNA load (low or high) were compared. The median pretreatment concentrations of pEBV DNA were 3440 copies/mL in 35 patients with stage III disease and 14, 900 copies/mL in 50 patients with stage IV disease ( P  = 0.059). The median concentration of pEBV DNA was 34, 500 copies/mL in 17 patients with relapse, which was higher than the concentration in 72 patients without relapse, who had a median level of 4985 copies/mL ( P  = 0.057). Further study showed that pretreatment pEBV DNA load was an independent prognostic indicator in pediatric NPC patients. High pEBV DNA was associated with adverse clinical outcomes, including PFS [3-year PFS rate = 80.5% versus 95.8%, hazard ratio (HR) = 5.00, 95% confidence interval (CI) = 1.00–25.00; P  = 0.050], DMFS (3-year DMFS rate = 80.5% versus 95.8%, HR = 5.20, 95% CI = 1.04–26.00; P  = 0.045), and OS (3-year OS rate = 82.9% versus 95.8%, HR = 5.41, 95% CI = 1.08–27.22; P  = 0.040). Pretreatment pEBV DNA load was an independent prognostic indicator for PFS, DMFS, and OS in pediatric patients with NPC. Prospective studies, however, are needed to validate these results. Abstract : Supplemental Digital Content is available in the text